BINA DESA 2025: Pelatihan Liputan dan Pelaporan dalam Upaya Penguatan Peran Remaja sebagai Citizen Journalist di Kampung Pekijing - Maspufatul Hija; Bangun Yoga Wibowo; Rochani Rochani (Pusat Riset dan Inovasi Nasional, 2026)
The BINA DESA 2025 program is a community service activity that aims to strengthen the role of teenagers as citizen journalists through training in coverage and reporting in the Pekijing Literacy Tourism Village, Serang City. This program was initiated due to the suboptimal documentation and publication of village activities through digital media, as well as the limited understanding of teenagers regarding the basics of journalism. The activity was carried out in three stages: preparation, implementation, and evaluation and monitoring. The training was conducted in three sessions using lectures, simulations, worksheets, and hands-on interviews in the field. Evaluation was conducted through pre-tests and post-tests, observation, and activity reflection. The results of the activity showed an increase in participants' understanding from an average pre-test score of 60% to 90% on the post-test. In addition to improving basic journalism understanding, this training also contributed to the development of youth career skills, such as communication skills, self-confidence, questioning skills, and cooperation. However, several obstacles were found, such as differences in participants' levels of understanding, time constraints, and unequal opportunities for practice.